M/G/1 QUEUE WITH SINGLE WORKING VACATION AND VACATION INTERRUPTION TO THE EXPECTED VALUE OF MANY CUSTOMERSAT BANK MUAMALAT SUKARAMAI SUB-BRANCH OFFICE - Susilowati, Rahmi; Lubis, Riri Syafitri; Widyasari, Rina (Pena Cendekia Insani, 2021)
Queuing occurs because the number of customers who arrive exceeds the service capacity, so customers have to queue to be served. A working vacation is a server serving at a slower speed. The server can return to a busy period with a (vacation interruption) opportunity or continue a vacation with a opportunity, with the single working vacation and vacation interruption method. The objective of this study is to obtain the effect of service rate and the expected value of the number of customers in the system after the departure of one customer and minimize operating costs during the vacation period (pause). The M / G / 1 queue study with Single Working Vacation and Vacation Interruption found that the average arrival rate (?) was 0.069 and the average service rate was 1.5 with the average vacation time (?) was 0, 41 and the average value of the expected number of customers in the system is 0,19 and for operating costs it can also be drunk to -16,38. This means that the queuing system is not efficient, due to the low level of server activity and the expected value of the number of customers in the system is 0 or there are no customers waiting in the system.